The validation of new formula of Islamic home financing among finance expertise’s - Puspa Liza, Ghazali; Sharifah Arni, Syed Jaaffar (2020)
Islamic banks in Malaysia practiced a different type of shariah principle that may offer advantage and disadvantages to Islamic home financing’s customer. Instead of analyzing the percentage of acceptance to Barakah Model Islamic home financing among public, a set of questionnaires were distributed among Islamic financial expertise. Barakah model need to be validate as to check it is fit according to Islamic finance’s need or not. The Barakah model is designed to cater the lower income earners especially RM 3500 and below with extra benefit to protect the house owner if anything happens in future.